The State of the Chinese Communist Youth League under Xi Jinping - Phuttivanich, Kittipos (Journal of East Asian and ASEAN Studies, 2024)
This article argues that under Xi Jinping’s leadership, Youth League faction (Qingniántuán: 青年团), Chinese Communist Party (CCP) members who came from Communist Youth League (CYL), has been tremendously intervened and restricted by Shanghai faction (Shànghăituán: 上海团), CCP members who came from local politics. These two factions have taken place in the CCP since Deng’s campaign of reform and opening-up. CYL is the Party organinzation dealing with youth affairs and CCP member recruitment. However, the growing numbers of CYL members and its increasing roles in youth affairs also caused other CCP members, especially those who come from locality to perceive CYL as their threat that the growing CYL would permanently dominate the Party. As Xi Jinping has been supported by Shanghai faction, the current status of CYL has been almost fully controlled by the Party, and the number of CYL member has been forced to reduce. As a result, CCP can still maintain its conservative way of the Party member recruitment and its governance for overall Chinese according to the CCP Constitution.